2021
DOI: 10.13057/biofar/f190204
|View full text |Cite
|
Sign up to set email alerts
|

Detection of terpenoids and steroids in Lindsaea obtusa with thin layer chromatography

Abstract: Abstract. Wutsqa YU, Suratman, Sari SA. 2021. Detection of terpenoids and steroids in Lindsaea obtusa with thin layer chromatography. Biofarmasi J Nat Prod Biochem 19: 65-69. The diversity of ferns on this earth is very high, and the potential and benefits for human life are ornamental plants, food materials, and medicines. The benefits of not all ferns are known because of the lack of information on these ferns, one of the ferns is Lindsaea obtusa J. Sm. Ex Hook. The phytochemical test is the first step in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…( 13 ) The steroids and triterpens identification was Liebermen-Bourchar test by adding chloroform, acetic anhydride, and H 2 SO 4 to the test tube. The formation of dark pink or red color or reddish brown in the lower layer indicated the presence of steroids and green color in the upper layer for triterpens ( 13 , 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…( 13 ) The steroids and triterpens identification was Liebermen-Bourchar test by adding chloroform, acetic anhydride, and H 2 SO 4 to the test tube. The formation of dark pink or red color or reddish brown in the lower layer indicated the presence of steroids and green color in the upper layer for triterpens ( 13 , 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…12 The Liebermen-Bourchar test were used to identify the steroids and triterpene and after chloroform, acetic anhydride, and H 2 SO 4 the extract would showed a dark pink or red color or reddish brown in the lower layer if it contained steroids and green color in the upper layer for triterpene. 12,13 Thin Layer Chromatography (TLC)…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…Steroids are part of fat groups therefore it tends to dissolve in non-polar solvents. Hence, steroids prefer to be extracted in polar and semi-polar solvents [22,23]. Steroids are present by using this method because of DES have multiple interactions such as hydrogen bonding, dipole-dipole, dipoleinduced dipole, Van der Waals (dispersion) and ion-dipole interactions that allow extraction of polar and non-polar components [24].…”
Section: Phytochemical Compounds Of Acmella Paniculata Leaf Extractmentioning
confidence: 99%
“…Steroids are present by using this method because of DES have multiple interactions such as hydrogen bonding, dipole-dipole, dipoleinduced dipole, Van der Waals (dispersion) and ion-dipole interactions that allow extraction of polar and non-polar components [24]. Next, terpenoid compounds also can be attracted to semipolar or even polar solvents as it possesses a hydroxyl group attached to the hydrocarbon chain [23]. The results found that both steroids and terpenoids are present in leaf extract of A. paniculata but not at an extremely high concentration.…”
Section: Phytochemical Compounds Of Acmella Paniculata Leaf Extractmentioning
confidence: 99%